Impact of livestock pricing policies on meat and milk output in selected sub-Saharan African countries - Williams, Timothy O. (International Livestock Centre for Africa, 1990)
Reviews, analyses and presents evidence concerning the effects of livestock pricing policies on production incentives in a sample of sub-Saharan countries including Cote d'Ivoire, Ethiopia, Mali, Nigeria, Sudan and Zimbabwe - selected on the basis of their livestock population, production, trade and consumption. Examines the growth and performance of the livestock sub-sector in the study countries. Demonstrates the diversity of situations and experiences with respect to production, consumption, export and import of livestock products. Considers the multiple objectives of price policies in the selected countries and analyses the principal instruments employed to influence producer and consumer prices. Highlights similarities and diversities in objectives and policies toward the livestock sub-sector and examines the compatibility of goals with instruments. Assesses the impact of government intervention on price incentives.